2015
DOI: 10.1097/sla.0000000000001032
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Surgeon-specific Reporting of Complications After Colectomy

Abstract: Objective We sought to determine the reliability of surgeon-specific postoperative complication rates after colectomy. Background Conventional measures of surgeon-specific performance fail to acknowledge variation attributed to statistical noise, risking unreliable assessment of quality. Methods We examined all patients who underwent segmental colectomy with anastomosis from 2008 through 2010 participating in the Michigan Surgical Quality Collaborative (MSQC) Colectomy Project. Surgeon-specific complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Finally, the choice to perform provider comparisons at the hospital level rather than the surgeon level was related to the inability to make statistically valid comparisons at the surgeon level due to (1) our agreement for use of the data, which did not allow for surgeon identifiers, and (2) small case volumes at the surgeon level. 14 Nevertheless, future work at the surgeon level may be possible (as the volume of available cases with this outcome increases with additional data collection).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the choice to perform provider comparisons at the hospital level rather than the surgeon level was related to the inability to make statistically valid comparisons at the surgeon level due to (1) our agreement for use of the data, which did not allow for surgeon identifiers, and (2) small case volumes at the surgeon level. 14 Nevertheless, future work at the surgeon level may be possible (as the volume of available cases with this outcome increases with additional data collection).…”
Section: Discussionmentioning
confidence: 99%
“…10–13 Until more generalizable studies are available which enumerate the most important risk-factors, 8 performing risk-adjusted comparisons between providers is not possible. 14 In addition, many studies utilize administrative data which rely on surrogates that may not capture ALs effectively. 15 The demonstration of variation in risk-adjusted rates of clinically defined AL between providers would be an important finding, indicating the potential for performance improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-and postoperative death is, however, very uncommon in elective colorectal surgery and this limits the value of assessing the statistical significance of one surgeon's practice. Shih et al [8] found that most surgeons do not perform enough colectomies (less than 56/year) to generate a statistically reliable surgeon-specific complication rate and concluded that underpowered results are unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have long attempted to profile provider performance, targeting different types of providers using various measures, with limited success. [1][2][3][4][5][6][7][8] Surgeons have been the focus of numerous profiling efforts focused on postoperative patient outcomes, dating back to the New York Department of Health's publication of mortality rates after coronary artery bypass grafting surgery in the early 1990s. 9 In 2013, the United Kingdom's National Health Service began publishing surgeon-specific patient outcomes.…”
mentioning
confidence: 99%